PP068 Stakeholder Views On Peer Review Of National Institute for Health Research Grant Applications. (2017) - Turner, Sheila; Lathlean, Judith; Chinnery, Fay; Moran, Rebecca; Guegan, Eleanor; Wyatt, Jeremy
Abstract : INTRODUCTION: It takes on average 17 years to translate a promising laboratory development into better patient treatments or services. About 10 years of this innovation process lies within the National Institute for Health Research (NIHR) research pathway. Innovations developed through research have both national and global impact, so selecting the most promising studies to fund is crucial. Peer review of applications is part of the NIHR research funding process, but requires considerable resources. The NIHR is committed to improving efficiency and proportionality of this process. This study is part of a wider piece of work being undertaken by NIHR (1) to reduce the complexity of the funding pathway and thus make a real difference to patients lives. METHODS: This study elicited the views of various stakeholders concerning current and possible future methods for peer review of applications for research funding. Stakeholder groups included: members of boards with responsibility for making funding decisions; applicants (both successful and unsuccessful); peer reviewers and NIHR staff. Qualitative interviews were conducted with stakeholders selected from each group, and results were analyzed and integrated using a thematic template analytical method. The results were used to inform a larger online opinion survey which will be reported separately. RESULTS: The views and insights of thirty stakeholders across the four groups about the peer review process of applications for funding will be presented. Findings generalizable to other funding programs outside the NIHR will be emphasized. The key themes which emerged included: strengths and weaknesses of applications, feedback, targeting and acknowledgement of peer reviewers. CONCLUSIONS: The results of our study of peer review processes carried out by one national research funder has relevance for other funding organizations, both within our country and internationally.